Template - Adilson Beatriz (Orbital: The Electronic Journal of Chemistry, 2022)
The standard style of Orbital should be followed. Prospective authors should consult any current issue of Orbital for examples of this style. The manuscript shall be prepared in accordance with the template available at: Template (New 2021)